Evaluation on the Legal Trade of Tokay gecko (Lacertidae; Gekkonidae; Gekko gecko Linnaeus, 1758) in Indonesia - Ari Ardiantoro; Amir Hamidy; Nia Kurniawan (Journal of Tropical Life Science, 2021)
Tokay gecko (Gekko gecko) is a large-sized gecko from the genus of Gekko, which is most commonly found from South Asia, southern China, and Southeast Asia. In Indonesia, these species are common to inhabit human-modified habitat in Sumatera, Borneo, Java, Bali, Lesser Sundas, Sulawesi, and Moluccas. In recent years, the demand for Tokay gekko with high use-value in both national and international markets has increased, one of which is used for traditional medicine. This situation raised the concern on the decreasing of the wild population and the validity of captive breeding programs that produced a large number of individuals. Several reports had estimated millions of individuals have been exported from Indonesia either legally or illegally, however, the exact number never been reported. The purpose of this study is to evaluate the trend on the harvested Tokay gecko and its origin based on the source code information. The data were collected from government records, including specimens harvested from the wild and specimens produced from captivity during 2013 - 2018 (six years). The results showed that the legally exported specimens were sourced from wild (W) and captive breeding (C or F). The total numbers of individuals exported from the wild harvest are 97.146, and all export realization is below the wild harvest quota. However, there are the large numbers of individuals exported and declared as specimens produced from the captive breeding facilities (6.965.000 with source code F, and 1.236.000 with source code C). More importantly, the high level of specimens produced from captive breeding facilities is unlikely to match with the biological capacity of this species. Therefore, we predict that specimens labeled captive breeding were likely sourced from the wild.